A portrait of adopted programming languages of Iberian Peninsula Higher Education Institutions - Sobral, Sónia Rolland (2021)
The definition of guidelines by international reference organizations (IEEE, ACM) in the design of higher education courses in Computer Science and Computer Engineering, means that each higher education institution may, or may not, follow these guidelines. However, the existence of national regulatory and quality control agencies (A3ES, ANECA) allows, in some way, to guarantee some systematization in the, for example, programming languages choices that each course can and should have. On the other hand, the software industry's pressure in conditioning programming languages to be taught in higher education institutions is another problem to be considered. The stress carried out by the reference organizations, supported by the national regulatory agencies and the software industry's pressure, does the exercise of adopting programming languages, quite complex. The objective of this article is to portray how Iberian Peninsula countries and hits higher education institutions have organized themselves to respond to the needs of professionals with competences in Computer Engineering, namely in terms of offering courses for students, but also in terms of programming language option chosen as initial, as well as the sequence of initial languages.